IMPLEMENTASI PENDIDIKAN ISLAM MULTIKULTURAL SEBAGAI UPAYA MENGATASI BIAS GENDER-BUDAYA DI DUNIA PENDIDIKAN - Setiawan, Yudhi; Hulaefi, Hulaefi; Musari, Musari; Mareta, Mira; Rabbani, Syarifah Aulia (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
This research aims to describe the phenomenon of gender and cultural bias that often occurs in the school environment and the application of ecological theory and multicultural Islamic education as a solution to overcome it. This research uses a type of library research by collecting and analyzing texts or documents that are relevant to the discussion that will be reviewed. Gender refers to the roles of men and women in society, while culture is a pattern of behavior and behavior that is passed from one generation to the next. Currently, there are many cultural and gender inequalities found in the school environment, both in the cultural treatment of teachers towards students who have different backgrounds and in lesson modules that marginalize the role of women. The results of the study show that the concpet of multicultural islamic education can be used by an educator in understanding cultural diversity and gender differences that occur in the world of education so that the learning process can go according to plan as well as puts understanding on students to accept and appreciate different values from different people, tribes, and cultures according to the context in the Qur'an and Sunnah.